A physics-based compact model of SiC power MOSFETs - Kraus, Rainer; Castellazzi, Alberto (IEEE, 2016)
The presented compact model of SiC power MOSFETs is based on a thorough consideration of the physical phenomena which are important for the device characteristics and its electrothermal behavior. The model includes descriptions of the dependence of channel charge and electron mobility on the charge of interface traps and a simple but effective calculation of the voltage-dependent drain resistance. Comparisons with both physical 2-D device simulations and experiments validate the correctness of the modeling approach and the accuracy of the results.